Perencanaan dan Implementasi Pendidikan Dengan Metode Nilai Tambah (LKP IT) Pada PKBM Hidayatul Mu’alimin Kota Sukabumi - Siti Nuraeni Mitra; Tintin Handiyati; Siti Qomariyah ; Siti Rahmawati ; Andi Sukandi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Implementing educational planning using the LKP IT value added method at PKBM is a strategic choice to increase students' excellence in the competitive IT labor market. PKBM Hidayatul Mu'alimin as a non-formal educational institution wants development, which requires a strategy to improve service quality, one of which is the existence of LKP IT (Information and Technology Skills and Training Institute). The aim of the research is to find out how PKBM Hidayatul Muta'alimin in Sukabumi City develops educational programs that are relevant to industrial needs and increase student competency in the competitive IT job market, as well as to obtain information regarding educational planning and implementation using the LKP IT value added method. The research method uses descriptive qualitative. The results of the research stated that the Planning and Implementation of Education using the LKP IT Value Added Method at PKBM Hidayatul Muta'alimin Sukabumi City stated that mapping the needs of the IT industry, integrated with elements of self-development and soft skills in the curriculum, the implementation of IT training education at PKBM focused on efforts in maximizing strengths and opportunities, in overcoming the weaknesses and threats of current education.